Numerical Solution of Nonlinear Fredholm Integral Equations by Using NKM and ADM - Hasan, MM; Matin, MA (Dhaka University Journal of Science, 2017)
In this paper, we present a numerical method to solve a non-linear Fredholm integral equations. We intend to approximate the solution of this equation by Newton-Kantorovich-quadrature method and Adomian Decomposition method compare both the methods accurately for solving the non-linear Fredholm integral equation. Dhaka Univ. J. Sci. 65(1): 61-66, 2017 (January)